Pengaruh Media Pembelajaran YouTube Terhadap Hasil Menulis Pengalaman Pribadi Siswa Sekolah Menengah Pertama - Tiffany, Billa Essa Surya; Ropiah, Opah (Jurnal Studi Guru dan Pembelajaran, 2024)
The objectives of this research are: 1) to describe the results of writing personal experiences before using YouTube learning media at SMP Negeri 1 Cibingbin class VII; 2) to describe the results of writing personal experiences after using YouTube learning media at SMP Negeri 1 Cibingbin class VII; 3) to describe the influence of YouTube learning media on writing personal experiences of students at SMP Negeri 1 Cibingbin class VII. This research is quantitative research. This research uses a quantitative approach to experimental research with a Pretest-Posttest one group design. The instruments in this research are pretest and posttest essay questions. Data analysis techniques use expert validation tests, normality tests, homogeneity tests and independent t-tests. The results of this research are: 1) student learning outcomes before using YouTube learning media are still far from the KKM (Minimum Provision Criteria) with an average score of 51.32; 2) student learning outcomes after using YouTube learning media have increased in accordance with the KKM (Minimum Adequacy Criteria) with an average score of 77.79; 3) the influence of YouTube learning media on the results of writing personal experiences at SMP Negeri 1 Cibingbin Class VII based on the paired sample t-test, Ha was accepted and Ho was rejected because the sig.(2-tailed) value was 0.000<0.05. So, it can be concluded that there is a significant influence between student learning outcomes before and after using YouTube learning media on the results of writing personal experiences.